Beautiful, Sexual, and Unimportant: The Situation of Female Inside and Outside the Game - Qingxian Chang (Art and Society, 2024)
In recent years, Japanese style animate download type mobile games have been extremely popular in the Chinese market. This paper explores gender dynamics in anime mobile games. Despite a growing presence of female gamers, the depiction of female characters within these games often meets traditional gender stereotypes: female characters are typically sexualized with limited diversity in their appearance, while male characters display a broader range of appearance and age. Using case study of the game Arknights, this research studies the male gaze in character design and the overlooked contribution of female players. It also uses discourse analysis to examine the wave of misogyny in the gaming community brought by Black Myth: Wukong.